2008
DOI: 10.1021/jo800637u
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Ring Contraction of Dibenz[b,f]azepin-5-yl Radicals: New Routes to Pyrrolo[3,2,1-jk]carbazoles

Abstract: Flash vacuum pyrolysis (FVP) of N-allyl- or N-benzyldibenz[b,f]azepine at temperatures from 750 to 950 degrees C gives pyrrolo[3,2,1-jk]carbazole as the major product. The mechanism of the ring contraction involves dibenzazepin-1-yl radical formation, followed by transannular attack and formation of a 2-(indol-1-yl)phenyl radical which cyclizes. The mechanism is supported by independent generation of 2-(indol-1-yl)phenyl radicals by two different methods, and the use of 1-(2-nitrophenyl)indole as a radical gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…However, we have recently shown that flash vacuum pyrolysis (FVP) of 1-(2-nitrophenyl)indole (1) at 875 8C leads to the formation of pyrroloA C H T U N G T R E N N U N G [3,2,1-jk]carbazole (2) via an aryl radical intermediate. [13] Application of this strategy to N-(2-nitrophenyl)carbazole [14] (3) readily gave IC (4) in a yield of 71 % on a gram scale, which is more than adequate for electrochemical film production (Scheme 1). This procedure is one step shorter than the method of Dunlop and Tucker and complements the range of substituted IC derivatives that can be synthesised.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we have recently shown that flash vacuum pyrolysis (FVP) of 1-(2-nitrophenyl)indole (1) at 875 8C leads to the formation of pyrroloA C H T U N G T R E N N U N G [3,2,1-jk]carbazole (2) via an aryl radical intermediate. [13] Application of this strategy to N-(2-nitrophenyl)carbazole [14] (3) readily gave IC (4) in a yield of 71 % on a gram scale, which is more than adequate for electrochemical film production (Scheme 1). This procedure is one step shorter than the method of Dunlop and Tucker and complements the range of substituted IC derivatives that can be synthesised.…”
Section: Resultsmentioning
confidence: 99%
“…For reference, a complete 1 H and 13 C NMR analysis of IC was carried out (see the Supporting Information). When IC was prepared by Dunlop and Tucker [12] it was thought that it would be bowl-shaped due to the strain in the central threering system and the preference for nitrogen to adopt a more trigonal pyramidal form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solvents were dried under standard conditions. Methyl o-iodobenzoate (1), [32] 2-methyl-6-phenylhexa-3,5-diyn-2-ol (2a), [14a] trimethyl(nona-1,3-diynyl)silane (2c), [33] 6-trimethylsilylhexa-3,5-diyn-1-ol (2d),…”
Section: Methodsmentioning
confidence: 99%
“…They are widely used as anticancer, antibacterial, DNA probe, antitumor, and so on. Therefore, many studies have been carried out on acridinedione derivatives. Tetraketones are extensively used as important precursors for the synthesis of various acridinediones.…”
Section: Introductionmentioning
confidence: 99%